(untitled) (Fiep Bulletin - online, 2016)
Research transversal descriptive field with students and parents in a public school in Fortaleza through questionnaires in order to ascertain the level of knowledge of this population with respect to knowledge about diabetes and exercise was performed.The sample of the research population consisted of 49 subjects of both sexes aged 15 to 59 years . The results showed that 50 % of respondents showed a good level of knowledge about the symptoms of diabetes ; regarding physical exercise and healthy diet in reducing the incidence and treatment of diabetes 47 % had no knowledge about it . As regards the question whether diabetes has no cure , 78 % said they did not , demonstrating a good knowledge of the subject , whereas with regard to information on diabetes in the media only 43 % reported that the subject is well discussed . It is concluded that despite the participants to give good knowledge on the subject there is still the need for interventions that address a greater number of individuals with information about the disease.